Vapor phase dealloying: A versatile approach for fabricating 3D porous materials. (15th January 2019) - Han, Jiuhui; Li, Cheng; Lu, Zhen; Wang, Hao; Wang, Zhili; Watanabe, Kentaro; Chen, Mingwei
Abstract: Three-dimensional porous materials with bicontinuous open porosity represent a new class of functional materials for various applications. Top-down dealloying has been demonstrated to be one of the most effective ways to fabricate 3D porous materials. Vapor phase dealloying, which makes use of the saturated vapor pressure difference between the constituent components in an alloy for selectively removing a less stable element or phase, is a promising versatile method for fabricating porous materials from active metals to inorganic elements. Here, using nickel-zinc and germanium-zinc alloys as the prototypes of single-phase and two-phase precursors, respectively, we report the fabrication of 3D bicontinuous porous Ni and Ge by vapor phase dealloying on the basis of selective element or selective phase evaporations. We also show the incorporation of vapor phase dealloying with chemical vapor deposition for the one-pot growth of 3D nanoporous graphene and the functional applications of vapor phase dealloyed porous Ge as Li ion battery electrodes. This study shines lights on the versatility of vapor phase dealloying for the fabrication of bicontinuous porous materials for a wide range of functional applications. Graphical abstract: Image 1